2016
DOI: 10.1016/j.ijgo.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Initial management of postpartum hemorrhage: A cohort study in Benin and Mali

Abstract: Decrease in the delays in oxytocin administration is a key determinant to improve maternal outcomes related to PPH in this context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…As a consequence, we excluded from our systematic review studies that used the former definition of S-PPH, such as Canadian and Italian studies. 41 , 42 Our systematic review covers a wide range of geographic areas including North and South America 20 , 18 , 15 , Southern and Northern Europe 14 -16 , 25 , 26 -23 , West Africa 27 and Israel. 21 It gathers a very large population, which provides Factors associated with severe postpartum haemorrhage: systematic review using Bradford Hill's causality framework Journal of Global Health Reports external validity and ensures extrapolations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, we excluded from our systematic review studies that used the former definition of S-PPH, such as Canadian and Italian studies. 41 , 42 Our systematic review covers a wide range of geographic areas including North and South America 20 , 18 , 15 , Southern and Northern Europe 14 -16 , 25 , 26 -23 , West Africa 27 and Israel. 21 It gathers a very large population, which provides Factors associated with severe postpartum haemorrhage: systematic review using Bradford Hill's causality framework Journal of Global Health Reports external validity and ensures extrapolations.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to oxytocin injected during labour, one study found a protective effect when injected within 10 minutes. 27 By contrast, Dupont et al found an overall increased risk of S-PPH (OR 1.26, 95% CI=1.06-1.50) 17 , while the study by Driessen et al, within the same Pi-thagore6-trial framework, established that this risk was actual when given beyond 20 minutes after birth (OR 1.49, 95% CI=1.14-1.94). 22 Given this inconsistency, oxytocin during labour was deemed as a factor of S-PPH of uncertain significance.…”
Section: Management Of Severe Pphmentioning
confidence: 92%
See 1 more Smart Citation
“…A survey recorded that the risk of severe PPH was still present even when the use of uterotonics was frequent. A cohort study conducted in Benin and Mali reported that administering oxytocin within 10 minutes of a PPH diagnosis was associated with a significant decrease in the risk of severe PPH. Shock and requiring a blood transfusion have been reported to be common near‐miss complications associated with obstetric hemorrhage, and that close monitoring of patients at risk for shock is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the World Health Organization (WHO) has recommended it for any vaginal birth since 2002. It is essential to ensure that the person who assists the mother during the birth is fully competent to progress towards the achievement of sustainable development goals [1] [7] [8]. Midwives and nurses are responsible for most deliveries in countries of sub-Saharan Africa [9].…”
Section: Introductionmentioning
confidence: 99%